PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KOTA PARIAMAN PROVINSI SUMATERA BARAT - Musri, Musri; Yendra, Musfi; Hose Pranando, Yuda (Universitas Ekasakti, 2023)
The study aimed to determine motivation, employee performance, and work environment that have a significant effect on the Personnel and Human Resources Development Agency (BKPSDM) Kota Pariaman. The method used in this research is descriptive with quantitative techniques. Data analysis used descriptive analysis, classical assumption test, and hypothesis test. The results of this study are Motivation and Work Environment affect the Performance of BKPSDM Employees in Pariaman City, West Sumatra Province. From this test, the R Square value is 95.8% where this figure indicates that Motivation and Work Environment affect the Performance of BKPSDM Employees in Pariaman City.